A new method for the experimental study of fatigue behaviour of thermoplastic materials - M. Basso; A. Crevatin; M. Celotto; M. Sanità (Fracture and Structural Integrity)
Nowadays most industrial realities undergo a strong push to improve cost-effectiveness, productivity and quality of manufactured products. In particular we focussed our attention in the area of design of plastic structural components, including both optimization of existing structures and design of new ones. In this case, but the following considerations have a more general value, these needs could be translated into demanding requirements of cost-effectiveness, weight reduction, reduced time-to-market with guarantee reliability. From a material perspective this means demanding mechanical performances, attention to safety margins and need of a better control of key design parameters. To obtain these results, we need to develop a new approach and effective tools in the design of plastic materials and components aimed at tailoring part behaviour to endurance and performance requirements. The target of the project is to find effective tools for predicting life endurance and damage evolution of plastic materials and components under mechanical/thermal service loading, in order to support the development of new material formulations and the design and optimization of structural components. In a particular way, we focussed our work in the characterization and modellization of materials durability and damage mechanisms. One of the main problems related to materials durability is due to fatigue failure. Fatigue process is a progressive weakening of a component with increasing time under load such that loads to be supported satisfactorily for short duration produce failure after long durations [1, 2, 3]. Fatigue failure should not be thought only as the breaking of the specimen into two separated pieces, but as a progressive material damage accumulation [2]. Material damage during fatigue loading manifests as progressive reduction of stiffness and as creep [5]. As standard fatigue testing are expensive in terms of money and time, it is essential to develop new approaches less time consuming and simpler to be implemented. One of the most important goals of the present work is the setting of an investigation method (Accelerated Fatigue Test) very simple to be implemented that is able to differentiate damage accumulation and durability performances of various material formulations in reduced time.